2012
DOI: 10.1007/s00216-012-6596-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance in immunoassay performance—comparison of different enzyme immunoassays for the determination of caffeine in consumer products

Abstract: Enzyme immunoassays with optical detection are amongst the most widely used bioanalytical tools. We defined seven parameters for the quality assessment of immunoassays that were addressed in a systematic study of direct and indirect immunoassays, using the enzymes horseradish peroxidase (HRP) and alkaline phosphatase (AP), the chromogenic substrates 3,3',5,5'-tetramethylbenzidine (TMB) and para-nitrophenyl phosphate, and the fluorescent substrates 3-(4-hydroxyphenyl)propionic acid and 4-methylumbelliferyl phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…All incubation steps were performed at room temperature on a Titramax 101 plate shaker (Heidolph, Schwabach, Germany) at 750 rpm (Grandke et al, 2013).…”
Section: Competitive Direct Elisamentioning
confidence: 99%
“…All incubation steps were performed at room temperature on a Titramax 101 plate shaker (Heidolph, Schwabach, Germany) at 750 rpm (Grandke et al, 2013).…”
Section: Competitive Direct Elisamentioning
confidence: 99%
“…Buffers (phosphate-buffered saline (PBS), tris(hydroxymethyl)aminomethane (TRIS), PBS-based and diethanolamine (DEA)-based washing buffers, sample buffer, and DEA substrate buffer), as well as calibrators were prepared and the same instruments (washer, shaker) were used as described in previous studies. 19,20 CBZ enzyme conjugate synthesis and coupling ratio analysis…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization time-of-ight (MALDI-TOF) mass spectrometry measurements were carried out as described by Grandke et al 19 Masses of 45 290 Da and 44 210 Da m/z for the single-charged species were determined for the CBZ-HRP conjugate and the unmodied HRP, respectively. The analyte derivative minus water has an m/z of 390 Da.…”
Section: Reagents and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satoshi Inouye reported that HRP had better precision but less linearity when compared with ALP . However, Julia Grandke's data supported another point of view that HRP was better than ALP . Thus, there was an interesting question as to which one system would be better when establishing a CLEIA method for a new target substance.…”
Section: Introductionmentioning
confidence: 99%